1988
DOI: 10.1016/s0380-1330(88)71574-9
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, Abundance, and Biomass of Freshwater Mussels (Bivalvia:Unionidae) in Lake St. Clair

Abstract: A mussel population survey was conducted in Lake St. Clair with divers using SCUBA to sample at 29 stations throughout the lake. Mean abundance was 2 m~2 and mean biomass was 4.4 g dry wt m~2. Of the 18 species collected, Lampsilis radiata siliquoidea was by far the most abundant, accounting for 45% of all individuals. The age-frequency distribution ofL. r. siliquoidea was dominated by individuals between 9 and 12 years old. In contrast, the second most abundant species, Leptodea fragilis, showed yearly variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
5

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 19 publications
2
30
0
5
Order By: Relevance
“…1980). However, an abundant and diverse mussel population still exists in Lake St. Clair (Nalepa and Gauvin 1988); this is probably because this lake is continuously flushed with high quality water from Lake Huron and oxygen concentrations remain close to saturation (Herdendorf et al 1986). Although conditions in the western basin have generally improved since the 1960s, as evidenced by a recovering Hexagenia population (Thornley 1985), it may take several decades before these improvements are reflected, if at all, in a recovery of the unionid population.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1980). However, an abundant and diverse mussel population still exists in Lake St. Clair (Nalepa and Gauvin 1988); this is probably because this lake is continuously flushed with high quality water from Lake Huron and oxygen concentrations remain close to saturation (Herdendorf et al 1986). Although conditions in the western basin have generally improved since the 1960s, as evidenced by a recovering Hexagenia population (Thornley 1985), it may take several decades before these improvements are reflected, if at all, in a recovery of the unionid population.…”
Section: Resultsmentioning
confidence: 99%
“…The greater "shockwave" of the Peterson, which blows away small organisms at the sediment surface just before impact, should not have any effect on these large, heavy-shelled forms. The effect is minimal even for the shelled but much smaller Sphaeriidae (Flannagan 1970, Nalepa et al 1988. While grab samplers generally underestimate unionid abundances (Haukioja and Hakala 1974, Isom and Gooch 1986, Nalepa and Gauvin 1988, any bias in abun- dance estimates should be reflected similarly in the three surveys.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…Leach (unpublished data) found 15 species of Trichoptera in Mitchell Bay . Nalepa & Gauvin (1988) found 18 species of bivalves in the lake with a total biomass of 4 .4 g DW m -2 . Both Hudson et al (1986) and Griffiths (1987) found 10 taxa of gastropods in the lake ; Leach (unpublished data) found 12 taxa in Mitchell Bay .…”
Section: Zooplanktonmentioning
confidence: 98%
“…Clair have been studied to various degrees by Hiltunen (1971), Hiltunen & Manny (1982), Thornley (1985), Hudson et al (1986), Griffiths (1987) Nalepa & Gauvin (1988) and Leach (unpublished data) . The benthic community is diverse .…”
Section: Zooplanktonmentioning
confidence: 99%